Poe’s Myth of Self: A Structural Barthesian Reading on “The Black Cat” and “The Murders in the Rue Morgue” - Khadafi, Bima Iqbal (Indonesian Journal of English Language Studies (IJELS), 2023)
This research analyzes how the narrative structure of Poe’s tales, namely “The Black Cat” and “The Murders in the Rue Morgue,” can be imposed with a certain idea about Self or the nature of human subjectivity. Poe’s tales illustrate that human subjectivity consists of two contrasting tendencies for destructiveness/imagination and reflection/cognition. They also show that the Self is always in tension with the Other. To counter this tension, Poe’s tales suggest that the Self should take a moment to reflect upon its subjectivity and let the Other reveal its alterity before interacting with it so that a more harmonious, or at least less problematic, relationship between the two can be established. Reading the selected stories using the Barthesian perspective, this paper sees this imposition as an act of myth-making which in itself is always ideological since there is a certain political and/or economic agenda driving it. Hence, the myth of Self in Poe’s tales needs to be demystified, a process through which Poe’s idea of Self is unmasked as his cries for those in power to take a moment of reflection about the mess they had put into the 1840s United States political-economic condition. This result implies that myths are not always constructed by the ruling class to justify its domination, but can also be written by the oppressed group to voice its concern. In this way, this paper subscribes to the Foucauldian notion of power.